Mysticism and/in the Old Testament: Methodological orientation and a textual example - Lombaard, Christo (HTS teologiese studies, 2015)
This contribution is the second in a series on methodology and Biblical Spirituality. In the first article, ‘Biblical spirituality and interdisciplinarity: The discipline at cross-methodological intersection’, the matter was explored in relationship to the broader academic discipline of Spirituality. In this contribution, the focus is narrowed to the more specific aspect of mysticism within Spirituality Studies. It is not rare for Old Testament texts to be understood in relationship to mystical contexts. One the one hand, when Old Testament texts are interpreted from a mystical perspective, the methods with which such interpretations are studied are familiar. The same holds true, on the other hand, if texts in the Old Testament, dating from the Hellenistic period, are identified as mystic. However, African mission history has taught us that the Western interpretative framework, based on ancient Greek philosophical suppositions (most directly the concepts rendered by Plato and Aristotle) and rhetorical orientations, is so strong that it transposes that which it encounters in other cultures into its terms, thus rendering the initial cultural understandings inaccessible. This is precisely the case too with Old Testament texts dating from pre-Hellenistic times, identified as mystic. What are the methodological parameters required to understand such texts on their own terms? In fact, is such an understanding even possible?